Pyrazole-Mediated C–H Functionalization of Arene and Heteroarenes for Aryl–(Hetero)aryl Cross-Coupling Reactions - Kundu, Abhishek; Dey, Dhananjay; Pal, Subhankar; Adhikari, Debashis (ACS Publications, 2021)
Herein we introduce a transition-metal-free protocol that involves a commercially available, inexpensive pyrazole molecule to conduct C–C cross-coupling reactions at room temperature via a radical pathway. Using this method, an aryldiazonium salt has been coupled to a wide range of arenes and heteroarenes including benzene, mesitylene, thiophene, furan, benzoxazole to result the corresponding biaryl products. The full reaction mechanism is elucidated along with the crystallographic probation of an active initiator species. A potassium-stabilized deprotonated pyrazole steers single-electron transfer to the substrate and behaves as an initiator for the reaction.
Only IISER Mohali authors are available in the record.
Keywords: C−H Functionalization; Cross-Coupling